Development of a Progressive Islam-Based Reading Literacy Training Model: An Analysis of Nasyiatul Aisyiyah Members’ Reading Competency - Yulia Adiningsih; Vismaia S. Damaianti; Yeti Mulyati; Dadang S. Anshori (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
The low reading literacy competency among Indonesian youth has raised concerns, highlighting the need for literacy development programs within organizations such as Nasyiatul Aisyiyah (NA), the female youth organisation of Muhammadiyah. This study aims to profile the reading literacy competency of NA members in Bogor Regency and explore ways to enhance their literacy practices. Using a mixed-method approach, both quantitative and qualitative data were gathered. A survey was distributed to NA members, covering demographic data, reading habits, reading proficiency, and access to reading resources. Additionally, in-depth interviews with organizational leaders were conducted. Quantitative data were analyzed using descriptive statistics, while qualitative data from interviews were examined through thematic analysis. The findings reveal that although many NA members have proficient reading skills, barriers such as inconsistent reading habits and limited access to quality materials persist. The study concludes that targeted literacy training programs aligned with the principles of Islam Berkemajuan (Progressive Islam) are essential to improving literacy skills while fostering religious values. These programs could enhance literacy outcomes for NA members and contribute to broader literacy efforts in Indonesia, forming the basis for a new training model tailored to NA’s needs.